Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2013)
This paper reviews recent developments in the status of financing for the Fund's concessional lending and debt relief. It presents the latest data available and projections whilst taking into account the pledges made thus far in response to the Managing Director's fund-raising requests of August 2009 and February and November 2012. Additionally, following the Executive Board's decision in September 2012, the PRGT's self-sustained capacity is discussed in the context of longer-term projections of the demand for concessional lending. Section II provides an overview of the Fund's concessional lending instruments and the associated financing framework as well as the developments since the October 2012 Update. Section III reviews the sources of financing for PRGT operations and discusses developments in the PRGT framework. Section IV reviews the use of PRGT resources and assesses the Trust's self-sustained capacity in light of the demand projections. Section V provides updates on the subsidization of emergency assistance, while Section VI presents the developments on the financing of debt relief under the HIPC, MDRI, and PCDR Trust. The paper concludes with a proposed decision completing the financing reviews of the PRG-HIPC and MDRI Trusts.